Effects of nanoplastics on microalgae and their trophic transfer along the food chain: recent advances and perspectives. Issue 12 (12th November 2021) - Zhu, Honglu; Fu, Shanfei; Zou, Hua; Su, Yanyan; Zhang, Yifeng
Abstract : Nanoplastics (NPs) have drawn increasing attention in recent years due to their potential threats to aquatic ecosystems. Abstract : Nanoplastics (NPs) have drawn increasing attention in recent years due to their potential threats to aquatic ecosystems. Microalgae are primary producers, which play important roles in the normal functioning of ecosystems. According to the source of production and laboratory experiments, both NPs and microalgae are likely to be widely found in various water environments, so they have a great chance of interacting with each other. Although tremendous efforts have been made to explore these potential interactions, a timely and critical review is still missing. In this paper, the effects of NPs on microalgae and their trophic transfer along the food chain are summarized. The toxic impact of NPs on microalgae is tightly associated with the concentrations, sizes and surface charge of NPs, as well as the microalgal species. In addition, NPs could also interact with many other contaminants, thus leading to combined effects on microalgae. NP exposure might block substance and energy exchange between microalgae and their surrounding environment, lead to a shading effect on microalgae, promote the production of reactive oxygen species (ROS) or induce direct physical damage on microalgae, thereby inhibiting the growth of microalgae. Moreover, NPs could also be trophically transferred along the food chain through microalgae and subsequently affect the species at a higher trophic level. Yet importantly, current understanding of the interactions between NPs and microalgae is still quite limited, and needs to be further studied.